Infection of Phytophthora palmivora from Soil in Cocoa Plantation - Agus Purwantara (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2008)
Phytophthora palmivora causes serious losses on cocoa in Indonesia and world-wide. The research aimed to assess the potential of soil as source of inocula for Phytophthora diseases in cocoa. Soil samples were baited using a healthy cocoa pod tissue, and the pathogen was isolated for morphological and molecular identification. Baiting technique was successfully used to detect the presence of P. palmivora in soil samples, and this was confirmed by morphological and molecular identification. P. palmivora can be detected in soil in all year around in wet areas indicating that soil is a massive and consistent source of inocula. Surveys conducted on the soil of Amazonian, Amelonado and Trinitario blocks of various ages showed that P. palmivora can be found in old and young cocoa blocks, even as young as 3 or 4 years. P. palmivora infection from soil to the pods appears to be mainly through contact or rain splash. Baiting with whole healthy pods exposed at different heights above undisturbed litter and above bare soil showed that the infection still occurred at 100 cm above the soil, even though it decreased gradually with the height. Infection from litter was not different to that from bare soil, indicating that the litter layer is not acting physically as a shield preventing rain from splashing the inocula up from wet soil to the pods. However, in tests for the possibility of P. palmivora carried through air convection, no pod was found to be infected, suggesting that the pathogen was not carried through convective accend of aerosol droplets from soil surface up to pods in the canopy.Key words : Theobroma cacao, pod rot, stem canker, baiting.